1988
DOI: 10.1182/blood.v72.3.886.bloodjournal723886
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation and identification of human monocytic colony-stimulating factor in human serum by enzyme-linked immunosorbent assay

Abstract: An enzyme-linked immunosorbent assay (ELISA) system for the quantitation of human monocytic colony-stimulating factor (hM-CSF) was established, which was based on the “dual antibody immunometric sandwich” principle using horse and rabbit polyvalent antibodies against human urinary colony-stimulating factor (CSF-HU). The minimal detectable level of hM-CSF was 10 U/mL, and the assays showed good reproducibility. As measured by this method, the average serum hM-CSF level of 20 normal adults was 540 +/- 110 U/mL (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

1991
1991
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(13 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…The M‐CSF level was determined by the sandwich enzyme‐linked immunosorbent assay (ELISA) method using three antibodies: equine antihuman M‐CSF antibody coated on a microtiter plate, an antibody solution containing highly purified rabbit antihuman M‐CSF antibody, and caprine enzyme‐conjugated antirabbit immunoglobulin G (IgG) antibody, according to the method reported by Hanamura and colleagues 16 . TP level was measured with a pyrogallol red‐molybdate complex reaction using a Micro TP‐AR Kit (Wako Pure Chemical Industries Ltd, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…The M‐CSF level was determined by the sandwich enzyme‐linked immunosorbent assay (ELISA) method using three antibodies: equine antihuman M‐CSF antibody coated on a microtiter plate, an antibody solution containing highly purified rabbit antihuman M‐CSF antibody, and caprine enzyme‐conjugated antirabbit immunoglobulin G (IgG) antibody, according to the method reported by Hanamura and colleagues 16 . TP level was measured with a pyrogallol red‐molybdate complex reaction using a Micro TP‐AR Kit (Wako Pure Chemical Industries Ltd, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of M‐CSF was measured by an radio­immunological method after raising anti‐M‐CSF antibodies in New Zealand rabbits 22−24 . Previous in‐house validation experiments had confirmed that non‐specific binding antibodies were less than 5% of the total population.…”
Section: Methodsmentioning
confidence: 99%
“…The M−CSF level was determined using the sandwich ELISA meth− od with three antibodies ± equine anti−human M−CSF antibody coated on a microtiter plate, an antibody solution containing highly purified rabbit antihuman M−CSF antibody, and caprine enzyme−conjugated anti−rabbit IgG antibody according to the method reported by Hanamura et al [18]. These antibodies origi− nated from the laboratory where Hanamura et al [18] worked.…”
Section: Determination Of M−csfmentioning
confidence: 99%